Thoracic outlet syndrome - Jasinskas, Mindaugas; Minderis, Mindaugas (Lietuvos chirurgija, 2015)
Thoracic outlet syndrome (TOS) is a symptom complex caused by compression of the brachial plexus, subclavian artery and/or vein at the level where these neurovascular structures pass from neck and thorax to upper extremity. Although it is not an uncommon disorder, unlike other peripheral compressive neuropathies in the upper extremity (median and ulnar nerve), thoracic outlet syndrome is usually undiagnosed. The pathology is caused by neck trauma, anatomical fibromuscular abnormalities in the thoracic outlet, repetitive stress injuries. Due to the anatomical peculiarities, the clinical presentation is distinguished by a huge variety of symptoms. Based on prevailing symptoms, thoracic outlet syndrome can be classified into 3 types: neurogenic, arterial and venous. Compression of the vessels alone occurs in only about 5% of cases. The main subjects of discussion are diagnosis and treatment. A reliable and objective diagnostic method is being searched for, according to which it would be possible to simply differentiate from other disorders with similar symptoms. In most of the cases the disorder cannot be seen using the visualisation methods or measured electrophysiologically, therefore some medical specialists do not acknowledge its presence. There is also a lot of controversy surrounding the treatment strategy. Although in literature the first rib resection is widely recommended as a way of operative decompression, other technically less complex surgical interventions are also of high efficiency. In this review, the literature data are summarised and supplemented with broad personal experience (reaching almost up to 600 cases). The attention is drawn to clinical peculiarities, which are not highlighted or not mentioned at all by other authors. The history of the term “thoracic outlet syndrome” is provided, relevant anatomical features, etiopathogenesis, clinical presentation and commonly used diagnostic and treatment methods are discussed.